Nandi figure in the Mandapa of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Mahakal Temple is a square, enclosed hall with simple stone walls, featuring pairs of pillars at the cardinal points and pilasters at the corners. In the center lies a platform with a Nandi statue. Adjacent to this, on the right-hand side, there is a small underground water passage. Above this passage, a raised platform can be accessed via a flight of steps. Notably, there is jali (lattice) work adorning this side of the mandapa.